The discovery of Silk Route: Cultural and technology communication between China, Korea and Japan - Teh, Pek Yen *; Goh, H. C. (UKM Press, 2016)
One of the earliest civilizations took place in Asia, particularly the East Asian region. As a main result of war, historical travel, such as trading and pilgrimage, influenced the daily life of most people in the region. The Han Dynasty was traced back as the most significant period that triggered travelling activities during the discovery of the Silk Road. Since then, travelling facilities were developed, which consequently led to the increased inter-region movement of people and merchants. This study explores the historical development of travels in Eastern Asia, with a particular focus on the expansion of the Silk Road throughout several dynastic periods of China, as well as its influence on peninsular Korea and Japan. This study concludes that the Silk Road is an important channel for the exchange of tangible and intangible elements between China, Japan, and peninsular Korea as a sinicization process, particularly in the exchange of food, papermaking, and printing technology. An increased understanding of Asia’s travel history helps to assess the travelling patterns in the region by revisiting the influence of tourists’ socio-demographic factors to include the cultural background with historical elements